Pattern of Temporomandibular Pain Dysfunction Syndrome - Sibtul Hassan, Muhammad Musa Cheema, Hammad Nasir Khan, Aroosa Khan, Sadia Hassan, Mahnoor Yasir (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The aim of this analysis was to understand the pattern of temporomandibular pain dysfunction syndrome among patients with TMPDS. Study Design: A descriptive cross-sectional study. Place and Duration: In the department of Oral and Maxillofacial Surgery, PIMS Hospital, Islamabad and Punjab Dental Hospital, Lahore for duration of Four months from 16th January 2021 to 15th May 2021. Methods: A total of 46 patients with a clinical demonstration of TMPDS were enrolled in the analysis. Data was collected on demographic characteristics, major ailments, etiology, history of stress and depression. Results: In this study, 18 (39.1%) of the 46 patients were male and 28 (68.9%) females. 17 to 70 years was the age range of patients with 24.3 ± 12.9 years mean age and 20 (43.5%) subjects in the 10-19 age group and then 9 (19.6%) patients in the 20-29 age group and 3 (6.5%) was observed in the 60-69 age group. Regarding the main complaint, pain was the most prevalent complain noticed in 34(73.9%) subjects. 7 (15.2%) patients reported click, limited mouth opening was observed in 5 patients (10.9%). Etiology was caused by facial trauma in 8 (17.4%) of 46 subjects and only 3 person (6.4%) reported Bruxism. Twelve patients (26.1%) have stress as the only etiology. Collectively stress was testified in 21 subjects (45.6%). The etiology could not be established in 14 (30.4%) patients. Nine stressed people used psychiatric medications for clinical depression (19.6%). Conclusions: In our analysis, TMPD was common in women with 25 years mean age. The most common underlying complaint was pain. Stress was the communal primary etiology. Also 23% have Clinical depression in stressed people.